2020
DOI: 10.1101/2020.01.16.908186
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative ‘omics approach to candidate pathogenicity factor discovery in the brain-eating amoebaNaegleria fowleri

Abstract: 3Red-Enfermedades Cardiovasculares (CIBERCV) 2 4 8= CSIRO Land and Water 2 5 9= CSIRO Land and Water, Black Mountain Laboratories 2 6

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…The current treatment regimen using miltefosine (MIL) and amphotericin B (AMB) was confirmed to be effective at inhibiting growth in vitro , which is in agreement with previous reports ( 20 23 ) and validates our assays performed to detect compounds that inhibit growth of Naegleria . The importance of fatty acid oxidation for N. fowleri was demonstrated in a recent in vivo study, as Herman et al observed upregulation of genes of N. fowleri involved in FAO after mouse passage ( 24 ). Our results now show that FAO inhibition is a valid target for new PAM therapy options, as etomoxir (ETO), perhexiline (PHX), and thioridazine (TDZ) showed total growth inhibition of N. fowleri .…”
Section: Discussionmentioning
confidence: 95%
“…The current treatment regimen using miltefosine (MIL) and amphotericin B (AMB) was confirmed to be effective at inhibiting growth in vitro , which is in agreement with previous reports ( 20 23 ) and validates our assays performed to detect compounds that inhibit growth of Naegleria . The importance of fatty acid oxidation for N. fowleri was demonstrated in a recent in vivo study, as Herman et al observed upregulation of genes of N. fowleri involved in FAO after mouse passage ( 24 ). Our results now show that FAO inhibition is a valid target for new PAM therapy options, as etomoxir (ETO), perhexiline (PHX), and thioridazine (TDZ) showed total growth inhibition of N. fowleri .…”
Section: Discussionmentioning
confidence: 95%
“…While reviewing the adaptations of Naegleria in the various environments, we cannot avoid discussing the potential role of AOX in the pathogenesis of N. fowleri . A recently published ‘omics approach investigating the potential genes that could be driving the pathogenicity of N. fowleri demonstrated up-regulation of mitochondrial energy conversion genes including those involved in ubiquinone biosynthesis, isocitrate dehydrogenase (TCA cycle), complex I and complex III of oxidative phosphorylation (Herman et al ., 2020). While the authors have demonstrated up-regulation of enzymes indirectly involved in oxidative stress pathway (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While the authors have demonstrated up-regulation of enzymes indirectly involved in oxidative stress pathway (e.g. agmatine deiminase), they were not able to demonstrate any significant change in the expression levels of any of the N. fowleri AOX homologs (Herman et al ., 2020). Based on these observations, it would be interesting to investigate the expression levels of AOX from the amoebas collected directly from the brain, either through transcriptomics and /or proteomics, as well as investigate whether this protein is essential for the survival of N. fowleri in such a complicated and variable environment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, with this genome, a phylogenomic analysis was carried out among the reported genomes of the genus Naegleria , placing the ATCC 30863 strain as the closest, followed by N. lovaniensis , while N. gruberi was found to be phylogenomically more distant [ 47 ]. In addition to the genomes described above, the sequences of N. fowleri strains “986” and “V212” were published in 2020, which will be described later [ 34 ].…”
Section: Omics Applications In Free-living Amoebaementioning
confidence: 99%
“…Although there is a possibility that some ORFs are poorly predicted, according to a recent study, they are more likely to be N. fowleri specific ORFs and emphasizes the importance of conducting molecular tests on them. Returning to the ORFs with identified homologs, it was observed that six of these encode functional proteins and that the rest contain recognizable conserved domains [ 34 ].…”
Section: Omics Applications In Free-living Amoebaementioning
confidence: 99%